(untitled) (Research, Society and Development, 2021)
The involvement of chronic diseases has occurred on a large scale, the lifestyle related to the genetics of individuals has resulted in greater numbers, with this the number of chronic renal patients has become increasingly greater. It is understood that the chronic renal patient undergoing dialysis treatment needs to know his rights, which can lead to an improvement in his social reality and health treatment, and the existence of a technological tool for support is of relevant existence. The study aimed to: Create a prototype software about the rights of chronic kidney patients undergoing hemodialysis. Methodology: Before carrying out the prototyping, a search was carried out in the databases, in order to discover the real need for the existence of the creation of the prototype, for this purpose the Scoping Review was carried out. The study was designed using a model of cyclic methodology, of prototyping. Results: The result was presented over three stages, which punctuate the stages of building a prototype. Through the development of the study, it was possible to create a prototype software about the rights of chronic renal patients undergoing hemodialysis. Conclusion: It is concluded, therefore, that the objective of the study was concluded, considering the creation of the prototype. The prototype has great possibilities of impact on the target population, since it comes to add more as another tool for maintaining the rights of chronic kidney patients.